I'm Black when I'm singing, I'm blue when I ain't and other plays - Sanchez, Sonia, 1934- (e-Duke books scholarly collection., 2010)
A collection of Sonia Sanchez's plays along with a historicizing introduction and critical essays on Sanchez's work.